Eficacia de la normativa ecuatoriana frente a la violencia filio-parental - Coello Canchignia, Cynthia Guadalupe (2025)
The study analyzes the effectiveness of Ecuadorian regulations in relation to child - parent violence (FPV), since there is currently an increase in violence in various forms, such as child abuse, intimate partner violence and, more recently, a notable increase in cases of aggression by children against parents. The main objective was to evaluate the effectiveness of the Ecuadorian legal framework to address this type of violence. The methodology employed was qualitative in nature, as it focused on the characterization and analysis of the causes of the phenomenon, using grounded theory, review of national regulations and comparison with regulations in other countries. In conclusion, it was determined that it is essential to propose legal reforms that establish a specific regulatory framework, including clear protocols for action to address this problem.